Please help me, I am drowning! The cry of parents of adolescents with a substance use disorder - Meriam M. Shadung; Paul R. Mbedzi; Rebecca M. Skhosana (AOSIS, 2024)
Background: Substance use disorders (SUDs) are on the rise among adolescents worldwide, including in South Africa, causing a significant challenge to parents. Regardless of the difficulties associated with SUDs in adolescents and their impact on parents, current studies on substance addiction have focused on diverse fraternities, excluding social work services for parents of adolescents with SUDs. Aim: To develop an in-depth understanding of social work services provided to parents of adolescents with SUDs. Setting: The study was conducted in two districts, Capricorn and Waterberg, in Limpopo province, South Africa. Methods: A qualitative research method using exploratory and descriptive designs was employed. The scheduled interview guides facilitated semi-structured interviews with 11 social workers and 8 parents. For data analysis, Tesch's eight steps were used. Results: Six themes emerged from the study: (1) social work interventions for parents, (2) family and community-related obstacles, (3) organisation-related obstacles, (4) substance use intervention strategies received by parents, (5) parents' coping mechanisms in dealing with adolescents with SUDs and (6) factors hindering access to social services. Conclusion: The findings show that the government, particularly the Department of Social Development as the custodian of social services, is obliged to develop and design standard guidelines for services to parents of adolescents with SUDs and to provide uniform services to social workers. Contribution: The study benefits the social work profession, particularly in the field of substance abuse because it generates effective parameters for services for parents of adolescents with SUDs.